Cyclo-VEGI inhibits bronchial artery remodeling in a murine model of chronic asthma. (26th November 2021) - Kim, Kyung Hoon; Hur, Jung; Lee, Hwa Young; Lee, Eung Gu; Lee, Sook Young
Abstract: Purpose/Aim: In the context of asthma, airway bronchial remodeling and angiogenesis in the bronchial mucosa are well established. Cyclopeptidic-vascular endothelial growth inhibitor (cyclo-VEGI) is an inhibitor of the vascular endothelial growth factor (VEGF) receptor that increases the proliferation of endothelial cells and the formation of new vessels. However, changes in the bronchial arteries of patients with asthma have not been clearly elucidated. We investigated whether structural changes occurred in bronchial arteries, as well as the effects of cyclo-VEGI in a mouse model of chronic asthma ( in vivo ) and human fibroblasts ( in vitro ). Materials and Methods: A validated mouse model of allergic airway inflammation with ovalbumin (OVA) as the causative allergen was used for the study. Mice were treated with cyclo-VEGI or fluticasone during OVA challenge. In vitro experiments were conducted to determine whether fibroblasts proliferated following elastin exposure and the effects of cyclo-VEGI on them. Results: OVA sensitization and challenge led to greater perivascular smooth muscle area, more elastic fibers, and elevated expression of vascular cell adhesion molecule (VCAM)-1 antigen. These phenomena indicated changes to bronchial arteries. Cyclo-VEGI and fluticasone treatment both inhibited airway hyper-responsiveness and inflammation. Cyclo-VEGI-treated mice exhibited decreased perivascular smooth muscle area, elastin fibers, and VCAM-1 expression. Fluticasone-treated mice exhibited reductions in perivascular smooth muscle but not in perivascular elastin or VCAM-1 expression. In vitro, fibroblast proliferation was enhanced by elastin treatment, which was inhibited by cyclo-VEGI treatment. Eotaxin expression was elevated in elastin-treated fibroblasts and decreased with cyclo-VEGI treatment. Conclusions: Vascular remodeling occurred in our mouse model of chronic asthma. Cyclo-VEGI could reduce airway inflammation and hyper-responsiveness by inhibiting VCAM-1 expression and elastin deposition around the bronchial arteries.